Mutant Transcriptome Sequencing Provides Insights into Pod Development in Peanut (Arachis hypogaea L.) - Wan, Liyun; Li, Bei; Lei, Yong; Yan, Liying; Ren, Xiaoping; Chen, Yuning; Dai, Xiaofeng; Jiang, Huifang; Zhang, Juncheng; Guo, Wei; Chen, Ao; Liao, Boshou (Frontiers in Plant Science, 2017)
Pod size is the major yield component and a key target trait that is selected for in peanut breeding. However, although numerous quantitative trait loci (QTLs) for peanut pod size have been described, the molecular mechanisms underlying the development of this characteristic remain elusive. A peanut mutant with a narrower pod was developed in this study using ethyl methanesulfonate (EMS) mutagenesis and designated as the “pod width” mutant line (pw). The fresh pod weight of pw was only about 40% of that seen in the wild-type (WT) Zhonghua16, while the hull and seed filling of the mutant both also developed at earlier stages. Pods from both pw and WT lines were sampled 20, 40, and 60 days after flowering (DAF) and used for RNA-Seq analysis; the results revealed highly differentially expressed lignin metabolic pathway genes at all three stages, but especially at DAF 20 and DAF 40. At the same time, expression of genes related to auxin signal transduction was found to be significantly repressed during the pw early pod developmental stage. A genome-wide comparative analysis of expression profiles revealed 260 differentially expressed genes (DEGs) across all three stages, and two candidate genes, c26901_g1 (CAD) and c37339_g1 (ACS), responsible for pod width were identified by integrating expression patterns and function annotation of the common DEGs within the three stages. Taken together, the information provided in this study illuminates the processes underlying peanut pod development, and will facilitate further identification of causal genes and the development of improved peanut varieties with higher yields.